PROFIL URINALISIS PASIEN HIPERTENSI DALAM KEHAMILAN Di Bagian Obstetri dan Ginekologi RSUD Ulin Banjarmasin Periode Juni 2021-Mei 2022 - Iman, Muhammad Nur; Nizomy, Ihya Ridlo; Rosida, Azma; Armanza, Ferry; Hendriyono, Franciscus Xaverius (Homeostasis, 2023)
Hypertension disorders in pregnancy (HDP) is one of the most common complications in pregnancy forming a triad along with bleeding and infection which are the main causes of maternal and prenatal morbidity and mortality. Urinalysis examination is one of the important laboratory tests in the diagnosis of HDP, especially to identify the presence of preeclampsia which can lead to eclampsia. Through urinalysis it can be seen the presence of protein in the urine which is one of the diagnostic criteria for preeclampsia-eclampsia and assessing kidney function during pregnancy. The purpose of this study was to determine the urinalysis profile of hypertensive patients in pregnancy. This study used an observational research design with a cross-sectional approach, using secondary data from medical records. This study used the entire population according to the inclusion and exclusion criteria. The subjects of this study were 69 patients. The results showed that preeclampsia was the most common type of HDP, namely 122 people (59.2%). Based on the results of urinalysis in Preeclampsia, the results of urinalysis that showed the most positive results were proteinuria, namely Trace 4 people (9.8%), 1+ 10 people (24.4%), 2+ 10 people (24.4%), and 3+ 4 people (9.8%). Whereas in Preeclampsia Superimposed Hypertension showed the same results where proteinuria was the most positive, namely Trace 1 people (5.9%), 1+ 3 people (17.6%), and 2+ 8 people (47.1%).